ANDROID-BASED GEOGRAPHY INFORMATION SYSTEM AND TOURISM OBJECT LOCATIONS (A CASE STUDY: FAKFAK REGENCY, WEST PAPUA PROVINCE) - Riyadh Arridha; Andi Roy (Jurnal Mantik, 2021)
Android Application is one of an effective, efficient, and innovative way as promotional media. The rapid development of technology makes Android as an option for delivering information easily by the target audience. Currently, Fakfak district has not widely known by tourists, but there are still tourists in finding these tourist sites. Therefore, it needs a media that provides information on the location of tourism in Fakfak district. This android application is included a way that can promote effectively and efficiently. This Android-based tourists location information system application aims to make easier for the tourists in finding tourism locations in Fakfak. So, it made easier for tourist to find any tourist destinations in Fakfak. This approach methodology used is a SWOT analysis by understanding all the information in a problem. The analysis is in the form of strategic planning which is used to evaluate the strengths, weaknesses, opportunities, and threats in a design process. So, the selection of android application media was more affective and the message to be conveyed was easily understood by the target audience. The result of this tourist location information system began with a choice of 12 tourist location areas in Fakfak. After selecting the home menu, all choices of tourist attractions in Fakfak will appear and when the desired tourists spot is selected, a tourist information will appear, tourist pictures and maps navigator that serves to direct the audience to the desired tourist spot.